Therapeutic potential of Garcinia kola with reference to the restoration of inhibited acetylcholinesterase activities in induced Clarias gariepinus - T.O. Ikpesu (Beni-Suef University Journal of Basic and Applied Sciences, 2014)
This study was conducted to assess the antidotal prospect of Garcinia kola seeds extract in restoring the activity of inhibited Acetylcholinesterase. This was done by inducing Clarias gariepinus with the enzyme inhibitor (glyphosate pesticide formulation). The fish divided into six groups were exposed different treatments; the pesticide alone, the G. kola seed extract alone and different mixture of the pesticide and G. kola seeds extract. AChE activities in the brain, liver and serum of the fish were measured in the experimental and control fish on day −7, 14, 21 and 28th by the colorimetric method. The enzyme was significantly (p < 0.05) inhibited in the glyphosate formulation test alone and in group IV treatment (0.16 mg/L glyphosate formulation with 150 mg/L of extract). The inhibition percentages of AChE ranged for the brain, liver and serum between 40.7–59.4%, 50–57% and 27.5–51.3%, respectively. The AChE activities were however, recovered in G. kola seeds extract treated aquaria, and were dose, time dependent and organ specific. Modifications of this enzyme may leads to increased perspiration, increased salivation, tearing, blurred vision, abdominal cramping, diarrhea, and if severe enough, death from respiratory depression. This investigation had revealed the therapeutic significance of G. kola seeds extract, by stabilizing the enzyme activity in the investigated fish. Further investigation is required to measure the concentrations of acetylcholine at cholinergic synaptic junction in fish and mammals induced with ant-cholinesterase agent and the possibility of its restoration using G. kola seeds.